Estabilidade e potencial antioxidante de microcápsulas de ficocianina - Formigheri, Mariana da Silva (2017)
Interest in bioactive compounds research has increased as consumers look for natural products that result in health benefits. The stability of these compounds, in the great majority, however is of unknown behavior. The use of techniques to ensure the functionality of these assets for different purposes becomes very important. Encapsulation is a technology capable of protecting the active substance from a wide range of exposure conditions, promoting controlled release, masking unpleasant odor and taste, and promoting the homogenous dilution of the encapsulated material in food products or pharmaceutical formulations. Phycocyanin is a phycobiliprotein, present in the cyanobacterium Spirulina platensis, and has been reported to have different functional properties, among them, the antioxidant. The objective of this study was to study the microencapsulation by spray-drying of phycocyanin, using the encapsulant maltodextrin, in stability tests and antioxidant potential in vitro and in vivo, in Saccharomyces cerevisiae cells. The results show that the encapsulation process produced spherical microcapsules of average size of 10 µm, with water solubility around 91.71%, water and moisture activity of 0.209 and 3.975%, respectively. Maltodextrin protected the active's physical agent temperature and promoted gradual release of the antioxidant potential and maintained the same after drying. In the in vivo tests the microcapsules statistically increased the enzymatic activity of glutathione and decreased levels of lipid peroxidation. It was concluded thatthe technique of encapsulating phycocyanin by spray dryer with the encapsulant maltodextrin was effective in maintaining the antioxidant activity of bioactive.